Translation of Substitution Units from English into Bahdini Kurdish - Siddiq, Najim A.; Khalel, Ahmad R. (Academic Journal of Nawroz University, 2017)
Substitution is a phenomenon that exists in almost all languages. It is a technique usually used in linguistics to refer to the process of permutation of one feature of the previous expression. Each language has its specific substitutional units which are used to avoid repetition and to make the text more cohesive. Translating substitutive units from English into Bahdini Kurdish pose some problems for translators if they do not have a good knowledge of the substitutional units. This study, therefore, aims at studying substitutions units in both English and Bahdini Kurdish. It also attempts to show the similarities and differences between the two languages and to examine some problems that stem from translating substitutive unit from English into Bahdini Kurdish. The study hypothesizes that context, in which substitutive units occur, plays an important role in governing these units.